Indo-muslim cultures in transition - Patel, Alka; Leonard, Karen (New Delhi : Manohar, 2025)
The authors in this volume explore Indo-Muslim cultures developing in South Asia from the sixteenth through twentieth centuries, sharing central themes but showing significant contextual variations by time and place. They focus a much-needed analytical gaze on the rich layers of circulation and exchange of art, architecture, and literature within South Asia and testify to the interaction of Muslims and Islamic traditions with other people and traditions in India for centuries.
Keywords: Mogul Empire -- Congresses -- History; SOCIAL SCIENCE / Minority Studies; India -- Congresses -- Civilization -- Islamic influences -- 1200-1765